2019
DOI: 10.4103/jpbs.jpbs_183_18
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of pregnant women on the use of daily low-dose aspirin in different hypertensive pregnancy disorders: A retrospective comparative study

Abstract: Background: Hypertensive disorders represent major causes of maternal and fetal complications. It includes a range of conditions, most notably preeclampsia. Aspirin is a well-accepted therapy for the primary and secondary prevention of cardiovascular events. The indications for the use of aspirin during pregnancy are, however, the subject of much concern. This study aimed to assess the clinical characteristics from the benefits of daily low-dose aspirin administration alongside antihypertensive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Urine protein tests are negative, and some patients may experience epigastric discomfort or platelet abnormalities. Severe gestational hypertension is defined as systolic blood pressure ≥ 160 mmHg and/or diastolic blood pressure ≥ 110 mmHg [ 18 , 19 ].…”
Section: Experiments and Analysis Of Adjuvant Therapy With Vitamin E ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Urine protein tests are negative, and some patients may experience epigastric discomfort or platelet abnormalities. Severe gestational hypertension is defined as systolic blood pressure ≥ 160 mmHg and/or diastolic blood pressure ≥ 110 mmHg [ 18 , 19 ].…”
Section: Experiments and Analysis Of Adjuvant Therapy With Vitamin E ...mentioning
confidence: 99%
“…Therapy with Vitamin E and Astragalus Severe gestational hypertension is defined as systolic blood pressure ≥ 160 mmHg and/or diastolic blood pressure ≥ 110 mmHg [18,19].…”
Section: Experiments and Analysis Of Adjuvantmentioning
confidence: 99%
“…In the study findings of Ayala et al ,[ 18 ] the BP readings were stable until the 22 nd week of pregnancy and then showed a significant linear BP increase in the second half of pregnancy; such complications could be protected from a single daily use of low-dose aspirin. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%